An Empirical Study on Reverse Psychology Applied in Advertising Messages - Chan, Winslet Ting Yan; Leung, Chi Hong (Asian Journal of Empirical Research, 2018)
Reverse psychology, also known as psychological reactance, is a social influence tactic that encourages people to act the opposite of what it is suggested. This technique has been applied by marketers in advertising in which a negative message or tagline (e.g., “you don’t buy the product) is used to motivate consumers to make purchase. Psychological reactance theory advocates that reactance occurs when people react to restore a freedom when it is eliminated or threatened to be eliminated. The expected response to an advertising message of not doing something is to do it. An experiment was designed to measure if 52 subjects were comfortable with negative advertising messages yet felt interested in them. Results showed that 49.7% of subjects were interested in these messages, although 76.6% of them were uncomfortable with the negative advertising messages. Results suggested that the application of reverse psychology tactic in advertising enable marketers to create awareness and raise interest of consumers. It is also interesting to find out that 40.8% of subjects were uncomfortable with the messages but showed interest in them. The practical way of using reverse psychology in advertising is discussed at the end of paper with an example for illustration.